2008
DOI: 10.1371/journal.pone.0003999
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Mechanism of Two Naphthoquinones (Menadione and Plumbagin) in Saccharomyces cerevisiae

Abstract: BackgroundQuinones are compounds extensively used in studies of oxidative stress due to their role in plants as chemicals for defense. These compounds are of great interest for pharmacologists and scientists, in general, because several cancer chemotherapeutic agents contain the quinone nucleus. However, due to differences in structures and diverse pharmacological effects, the exact toxicity mechanisms exerted by quinones are far from elucidatation.Methodology/Principal FindingsUsing Saccharomyces cerevisiae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 28 publications
6
95
0
4
Order By: Relevance
“…Previous studies reported that plumbagin regulates the cellular redox state by modulation of GSH (36,39). In this study, we observed the content of GSH in Kasumi-1 cells treated by plumbagin for 6 and 12 h. The content of GSH was significantly decreased in groups of plumbagin treatment.…”
Section: Gsh Depletion By Plumbagin Increases the Production Of Rosmentioning
confidence: 47%
“…Previous studies reported that plumbagin regulates the cellular redox state by modulation of GSH (36,39). In this study, we observed the content of GSH in Kasumi-1 cells treated by plumbagin for 6 and 12 h. The content of GSH was significantly decreased in groups of plumbagin treatment.…”
Section: Gsh Depletion By Plumbagin Increases the Production Of Rosmentioning
confidence: 47%
“…These QM intermediates react preferentially with GSH, leading to GSH depletion, which can cause death of both tumorigenic cells, as well as normal cells, depending on the cell lines. The QMs derived from naphthoquinones drugs (29-32 and 51) promote oxidative stress by a nucleophilic attack on GSH, as do also other quinoid compounds, such as menadione and plumbagine [98]. This has also been demonstrated with "simpler" derivatives of naphthoquinones, produced by photochemical reactions (83 and 86, see Fig.…”
Section: Drugs That Release Qms That React Preferentially With Proteimentioning
confidence: 94%
“…21 Assim, quinonas e seus produtos de redução (semiquinonas e hidroquinonas) são de interesse toxicológico devido à sua habilidade para gerar ERO [ânions radicais superóxidos (O 2 -), radicais hidroxila (·OH), peróxido de hidrogênio (H 2 O 2 ) e oxigênio singlete ( 1 O 2 )], as quais podem causar danos em membranas, proteínas e no DNA, podendo induzir a apoptose e, entre outros, a carcinogenese. 9,11,12 Relatos de experiências in vivo, 11,22 por exemplo, têm provado a natureza carcinogênica dessas substâncias sob determinadas condições. Em função disso, as quinonas são associadas com a incidência de vários tipos de câncer em humanos.…”
Section: Participação Em Reações Do Ciclo Redoxunclassified
“…[1][2][3][4][5] Vários estudos demonstram os efeitos tóxicos e deletérios de quinonas para o organismo humano (indutor de várias doenças tais como câncer de pulmão, asma e inflamação alérgica), podendo também atuar como inibidora de enzimas importantes em sistemas celulares reparadores, causarem danos genéticos etc. [5][6][7][8][9][10][11] Por outro lado, as quinonas apresentam interesses toxicológicos e farmacoló-gicos consideráveis. 12,13 Estudos revelam variadas biodinamicidades, destacando-se, dentre muitas, a participação em processos bioquími-cos vitais, 6,14,15 a sua produção por insetos e vegetais como defesa química 16,17 além de atuarem como microbicidas, anticancerígenos e antiangiogênicos (Figura 1).…”
Section: Introductionunclassified
See 1 more Smart Citation